Golf-Putting Performance in Skilled Golfers at Different Distances to the Hole - Dias, Gonçalo (2021)
Golf putting occurs under highly variable conditions. Therefore, adapting to different putting distances is a challenge that the golfer faces and understanding the variables underlying performance in this task is important. The main objective of this study was to analyse the golf-putting performance in skilled golfers at different distances to the hole. Fourteen highly skilled golfers, adult male and right-handed (41.5 13.2 years with an average handicap of 2.3 1.7) performed the golf putting on a natural grass green, completing a total of 120 randomly ordered trials, 30 trials at each of the four different practice conditions (1, 2, 3, and 4 m away from the hole). A smart engineered putter (InPutter) was used as the data acquisition instrument to record several process variables at 100 Hz. Results indicated that golf-putting distances constrained movement organisation variables in specific ways. For example, as the distance to the hole changes, so do the informational constraints, shaping how a golfer needs to regulate performance. We concluded that the effects of different golf-putting distances required the implementation of functional solutions uniquely adjusted to each player. Furthermore, the perception that the player withdrew from the properties of the context (e.g., distance to the hole) was important to adapt the golf-putting process variables (e.g., amplitude and duration of the movement, among others). All these factors led to a decisive influence on how the golfer hit the ball and adjusted his performance. A major implication of developing a better understanding of the role of performance in golf putting is that coaches and players should allow functional movement behaviours to emerge during practice.